Improving Students' Problem-Solving Skills Using Direct Instruction-Oriented Worksheets on the Subject of Temperature and Heat - Hani Sapna; Sarah Miriam; Muhammad Hafiz Ridho; Suyidno Suyidno; Muhammad Saukani (Jurnal Ilmiah Pendidikan Fisika, 2023)
Problem-solving skills are among the key competencies in 21st-century life, yet they are poorly trained in schools. This study aims to produce a direct teaching-oriented temperature and heat worksheet that is feasible to use to improve students' problem-solving skills. The ADDIE design was used in the development of this worksheet. The worksheet was tested on 25 students in Class XI SMA. Data was measured using validation instruments, response questionnaires, and problem-solving tests. The results showed that the developed student worksheet was categorized as very valid, the student's response to using the worksheet was categorized as practical, and the student worksheet was categorized as effective because the N-Gain of problem-solving of 0.56 was categorized as moderate. This means that the developed direct teaching-oriented student worksheet is feasible to improve problem-solving skills. This student worksheet can be an alternative for teachers to equip 21st-century competencies, especially problem-solving skills.